Characterization of cellulose I/II hybrid fibers isolated from energycane bagasse during the delignification process: Morphology, crystallinity and percentage estimation. (20th November 2015) - Yue, Yiying; Han, Jingquan; Han, Guangping; Zhang, Quanguo; French, Alfred D.; Wu, Qinglin
Graphical abstract: Highlights: The revised highlights are as below: Cellulose I/II hybrid fibers were obtained during delignification process. Defibrillation effect with reduced fiber width was observed. The crystallinity for cellulose fibers decreased after NaClO2 treatment. XRD, 13 C NMR and FTIR results showed the same trend in the degree of crystallization. Abstract: Cellulose I, cellulose II and cellulose I/II hybrid fibers were prepared from energycane bagasse using NaOH and NaClO2 treatments. The definitive defibrillation effect with an average width of 12 ± 5 μm was observed for the fibers treated with 20 wt% NaOH for 10 h and NaClO2 for 2 h. The ribbon shaped cellulose I fibers were converted to a swollen state with a rougher surface by 20 wt% NaOH treatment for 10 h. The percentage of cellulose I decreased from 100% to 5%, and the corresponding CI values increased from 58.2% to 68.8% during the conversion from cellulose I to II. After further NaClO2 treatment, the CI values were decreased because of partial destruction of hydrogen bond network. XRD, NMR and FTIR results present the same trend in the degree of crystallization for all the samples.